Estimation of energy productivity change in Baltic Sea and EU non-Baltic Sea states - Ming-Chung Chang; Ching-Hua Yu (Baltic Journal of Economics, 2017)
The Baltic Sea states and the European Commission initiated the intergovernmental Baltic Sea Energy Cooperation (BASREC) in 1998 and established it the following year. The aim of this study is to examine and compare the energy productivity change, energy technical change, and energy efficiency change in Baltic Sea states and non-Baltic Sea states using the Malmquist-DEA approach. The main results indicate that energy productivity in the Baltic Sea states has been improved, with this mainly caused by energy technology progression; however, the improvement in energy efficiency is not so obvious. In addition, the subsample includes 10 former communist countries, showing that the source of their energy productivity change not only comes from energy technical change, but also energy efficiency changes. In other words, the catching up effect in the 10 former communist countries is more obvious than that in the Baltic Sea states.
Keywords: C52; Q43; 330; Baltic Sea states; Malmquist-DEA approach; BASREC; EU